"I think they discriminated against me": Using prototype theory and organizational justice theory for understanding perceived discrimination in selection and promotion situations - HARRIS, Michael M. (Institutional Knowledge at Singapore Management University, 2004)
Research in industrial/organizational (I/O) psychology has generally focused on objective measures of employment discrimination and has virtually neglected individuals' subjective perceptions as to whether a selection or promotion process is discriminatory or not. This paper presents two theoretical models as organizing frameworks to explain candidates' likelihood of perceiving that discrimination has occurred in a certain selection or Promotion situation. The prototype model stresses the importance of the prototypical victim-perpetrator combination, the perceived intention of the decision-maker, and the perceived harm caused as possible antecedents of perceived employment discrimination. In the organizational justice model, procedural, informational, interpersonal, and distributive fairness play a central role in determining candidates' perceptions of discrimination. The fairness heuristic helps to explain which type of fairness information dominates these perceptions. Applications and research propositions are discussed as well as the similarities and differences between the two models. We conclude by offering several factors that may determine which model is used in deciding whether or not discrimination has occurred.